Statistical Analysis and Determination of Representative Size for Sediment in Malaysian Urban Drains - Bong, Charles Hin Joo (UNIMAS Publisher, 2018)
This paper highlights the statistical analysis done on sediment samples collected from concrete drains in Malaysian major urban areas in order to understand the characteristics of the sediment and also to determine the suitable representative grain size. Samples were collected from 12 urban areas in Peninsular Malaysia and 1 urban area in East Malaysia and subjected to sieve analysis. Results from sieve analysis had shown that the major component of the sediment was sand with a mean value of 72.2%, followed by gravel with a mean of 24.7% and silt and clay with a mean of 3.1%. Samples from 10 locations have shown a non normal distribution with the tenderness to skew to the right. Due to this, the conventional use of median grain size, d50 as the effective size for sediment samples might not be a good representation for the sediment distribution. Further statistical analysis in this paper have suggested that the mode grain size is a much better representative grain size due to its stability when compared to median and mean size. Thus, a much better representative for the sediment samples from Malaysian urban areas would be the mode size (in this case is d20 ).